Experimental Investigation of Droplet Evaporation of Water with Ground Admixtures while Motion in a Flame of Liquid Fuel; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Dmitrienko M. A. Margarita Aleksandrovna; Nyashina G. S. Galina Sergeevna; Zhdanova A. O. Alena Olegovna; Vysokomornaya O. V. Olga Valeryevna (2016, 2016)
Title screen